2013
DOI: 10.1016/j.cca.2013.06.016
|View full text |Cite
|
Sign up to set email alerts
|

A new enzyme-linked immunosorbent assay system for human hepatic triglyceride lipase

Abstract: These results indicate that this new sandwich ELISA for measuring HTGL concentration in PHP can be applied in a daily clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
2
5
1
Order By: Relevance
“…The current findings that PHP-HTGL concentration showed a tendency toward inverse correlations with serum HDL-C (R = 0.285) were comparable with our previous study (11). On the other hand, there were no significant correlations of serum HTGL with HDL-C, which was an unexpected finding.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current findings that PHP-HTGL concentration showed a tendency toward inverse correlations with serum HDL-C (R = 0.285) were comparable with our previous study (11). On the other hand, there were no significant correlations of serum HTGL with HDL-C, which was an unexpected finding.…”
Section: Discussionsupporting
confidence: 88%
“…The results of immunoprecipitation analysis with MoAbs indicated the presence of HTGL in serum. Previously, we reported an ELISA system for measuring PHP-HTGL using two distinct MoAbs raised against recombinant human HTGL, which was not able to detect serum HTGL (11). However, it is labor intensive to collect large numbers of PHP samples in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A report by authors from USA showed that unlike wild type mice, HL KO mice showed no development of fat accumulation in the liver even after high fat diet being loaded 68) . This finding suggests that HL is not simply associated with the development of fatty liver but may have causal effect bolic disorders, and we found that there was a positive correlation between EL and HL concentrations 34) .…”
Section: Hl In Various Conditionssupporting
confidence: 55%
“…The post-heparin plasma was withdrawn 15 min after intravenous injection of 50 units of heparin/kg body weight (BW) for the assay of LPL along with the HTGL activity and concentration. The pre-heparin LPL and HTGL mass were determined with a highly sensitive and specific ELISA [20,21]. The LPL and HTGL activities were determined with the automated assay [22].…”
Section: Measurements Of Lipids Lipoproteins and Lpl Along With The mentioning
confidence: 99%